New species and records of Pyrgulopsis (Gastropoda: Hydrobiidae) from the Snake River basin, southeastern Oregon: further delineation of a highly imperiled fauna - Hershler, Robert; Liu, Hsiu-Ping (Zootaxa, 2009)
Here we describe two new species from southeastern Oregon based on morphologic and molecular (mtCOI) evidence. Pyrgulopsis fresti n. sp., commonly known as the “Owyhee hot springsnail” and long considered to be distinct and critically imperiled, lives in thermal springs along a short reach of the Owyhee River above Three Forks. This snail differs from other regional species in its squat shell; penial ornament consisting of a large, disc-shaped ventral gland; absence of a seminal receptacle; and mtCOI sequences. Pyrgulopsis owyheensis n. sp. ranges among five disjunct groups of springs in the Owyhee and Malheur river drainages and is occasionally sympatric with P. fresti. This snail is closely similar to another regional congener, P. intermedia (Tryon, 1865), but is smaller and further differentiated by its typically disjunct inner shell lip, longer and narrower penial filament, more distally positioned ventral gland of penis, and mtCOI sequences. The type locality (Owyhee Spring) population of P. owyheensis is genetically differentiated from the other geographical subunits of this species (1.5–1.8% sequence divergence) and should perhaps be managed as a separate conservation unit. New records are provided for P. intermedia which extends the range of this conservation priority species into the lower Owyhee River basin. We also show that the “Malheur springsnail,” which has been listed in various conservation-related publications and documents, is the same as P. intermedia. This study provides critical information for the conservation of springsnails in southeastern Oregon and underscores the need for additional field surveys in the region.